Revealing chlorinated ethene transformation hotspots in a nitrate-impacted hyporheic zone. (15th September 2019) - Weatherill, John J.; Krause, Stefan; Ullah, Sami; Cassidy, Nigel J.; Levy, Amir; Drijfhout, Falko P.; Rivett, Michael O.
Abstract: Hyporheic zones are increasingly thought of as natural bioreactors, capable of transforming and attenuating groundwater pollutants present in diffuse baseflow. An underappreciated scenario in the understanding of contaminant fate in hyporheic zones is the interaction between point-source trichloroethene (TCE) plumes and ubiquitous, non-point source pollutants such as nitrate. This study aims to conceptualise critical biogeochemical gradients in the hyporheic zone which govern the export potential of these redox-sensitive pollutants from carbon-poor, oxic aquifers. Within the TCE plume discharge zone, discrete vertical profiling of the upper 100 cm of sediment pore water chemistry revealed an 80% increase in dissolved organic carbon (DOC) concentrations and 20–60 cm thick hypoxic zones (<2 mg O2 L −1 ) within which most reactive transport was observed. A 33% reduction of nitrate concentrations coincided with elevated pore water nitrous oxide concentrations as well as the appearance of manganese and the TCE metabolite cis -1, 2-dichloroethene (cDCE). Elevated groundwater nitrate concentrations (>50 mg L −1 ) create a large stoichiometric demand for bioavailable DOC in discharging groundwater. With the benefit of a high-resolution grid of pore water samplers investigating the shallowest 30 cm of hypoxic groundwater flow paths, we identified DOC-rich hotspots associated with submerged vegetation ( Ranunculus spp.), where low-energy metabolic processes such as mineral dissolution/reduction, methanogenesis and ammonification dominate. Using a chlorine index metric, we show that enhanced TCE to cDCE transformation takes place within these biogeochemical hotspots, highlighting their relevance for natural plume attenuation. Graphical abstract: Image 1 Highlights: Vertical hyporheic flow paths show net declines in O2, NO3 and TCE concentrations. TCE chlorine index metric and PCA used to interpret pore water biogeochemistry. DOC-rich hotspots facilitate low-energy metabolism and cDCE production. High nitrate background concentrations dominate the stoichiometric demand for DOC.